Peran Pancasila sebagai Sumber Nilai dalam Pendidikan Karakter Bangsa - Ahmad Muhamad Mustain Nasoha; Akbar Raafi Ikhsani Choiri; Bianca Arvi Monteri; Hanifah Nur Istiqomah; Cahya Rahmadani; Argya Annisa Maheswari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the role of Pancasila as a source of values in national character education amid the challenges of globalization and digital disruption. Pancasila, as the ideology and foundation of the state, contains universal values derived from local wisdom and the nation's culture. However, the implementation of these values in formal education remains formalistic and does not sufficiently touch the internalization aspects of students. Through a descriptive-analytical qualitative approach with ideological and normative dimensions, this study involved teachers, students, and educational stakeholders in Central Java. Data collection techniques included interviews, observations, and document studies, with thematic analysis based on the principles of Pancasila and Islamic law principles. The study results indicate that Pancasila-based character education requires a pedagogical transformation that is contextual, participatory, and grounded in real-life experiences.Pancasila must be actualized as a way of life through adaptive educational practices, thereby forming a generation that is of integrity, responsible, and mature both morally and socially.